Hydrophobic interactions within the C terminus pole helices tunnel regulate calcium-dependent inactivation of TRPC3 in a calmodulin-dependent manner. (January 2023) - Wijerathne, Tharaka; Lin, Wei-Yin; Cooray, Akila; Muallem, Shmuel; Lee, Kyu Pil
Highlights: Hydrophobic interaction in the pole helix in TRPC3 is important for TRPC channel function. Mutation interrupting pole helix hydrophobic interaction attenuates calcium dependent inactivation. TRPC3 has calcium dependent feedback regulation either by direct biding of calcium to CBSs and calcium/calmodulin dependent regulation to CIRB. Abstract: Recent structural studies have shown that the carboxyl-terminus of many TRP channels, including TRPC3, are folded into a horizontal rib helix that is connected to the vertical pole helix, which play roles in inter-structural interactions and multimerization. In a previous work we identified I807 located in the pole helix with a role in regulation of TRPC3 by STIM1 (Lee et al., 2014, Liu et al., 2022). To further determine the role of the pole helix in TRPC3 function, here we identified key hydrophobic residues in the pole helix that form tight tunnel-like structure and used mutations to probe their role in TRPC3 regulation by Ca 2+ and Calmodulin. Our findings suggest that the hydrophobic starch formed by the I807-L818 residues has several roles, it modulates gating of TRPC3 by Ca 2+, affects channel selectivity and the channel Ca 2+ permeability. Mutations of I807, I811, L814 and L818 all attenuated the Ca 2+ -dependent inactivation (CDI) of TRPC3, with I807 having the most prominent effect. The extent of modulation of the CDI depended on the degree of hydrophobicity of I807. Moreover, the TRPC3(I807S) mutant showed altered channel monovalent ion selectivity and increased Ca 2+ permeability, without affecting the channel permeability to Mg 2+ and Ba 2+ and without changing the pore diameter. The CDI of TRPC3 was reduced by an inactive calmodulin mutant and by a pharmacological inhibitor of calmodulin, which was eliminated by the I807S mutation. Notably, deletion of STIM1 caused similar alteration of TRPC3 properties. Taken together, these findings reveal a role of the pole helix in CDI, in addition to its potential role in channel multimerization that required gating of TRPC3 by STIM1. Since all TRPC and most TRP channels have pole helix structures, our findings raise the possibility that the pole helix may have similar roles in all the TRP family. Graphical abstract: Image, graphical abstract